Causes of Microcephaly in the Zika Era in Argentina: A Retrospective Study. (August 2021) - Berberian, Griselda; Bologna, Rosa; Pérez, María Guadalupe; Mangano, Andrea; Costa, Marina; Calligaris, Silvana; Morales, María Alejandra; Rugilo, Carlos; Ruiz-Burga, Elisa; Thorne, Claire
There are gaps in understanding the causes and consequences of microcephaly. This paper describes the epidemiological characteristics, clinical presentations, and etiologies of children presenting microcephaly during the Zika outbreak in Argentina. This observational retrospective study conducted in the pediatric hospital of Juan P. Garrahan reviewed the medical records of 40 children presenting microcephaly between March 2017 and November 2019. The majority (60%) were males and born full-term. At first evaluation, microcephaly was defined as congenital (31/40, 77%) and associated with other features (68%) such as seizures, developmental delay, non-progressive chronic encephalopathy, and West Syndrome. It was found manifestations restricted to central nervous system (55%), ocular (8/40, 20%), and acoustic (9/40, 23%) defects, and abnormal neuroimaging findings (31/39, 79%). Non-infectious diseases were the primary cause of isolated microcephaly (21/37, 57%), largely related to genetic diseases (13/21, 62%). Only 3 were children were diagnosed with Congenital Zika infection (3/16, 7.5%).